Prediction of Vesicoureteral Reflux by Ultrasonography and Renal Scan in Children - Banafsheh Arad MD; Abolfazl Mahyar MD; Mahmoud Vandaie MD; Sonia Oveisi MD (SAGE Publishing, 2022)
Background. In recent studies, renal ultrasonography and dimercapto-succinic acid (DMSA) scan have a role in predicting vesicoureteral reflux in children with febrile urinary tract infection (UTI). Materials and Methods . Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (PLR), and negative likelihood ratio (NLR) were defined for ultrasonography and DMSA scan to predict vesicoureteral reflux in 70 children with febrile UTI. Results. Renal ultrasonography sensitivity, specificity, PPV, NPV, PLR, and NLR for vesicourethral reflux prediction was 0.57, 0, 1, 0, 0.57, and 0.47 and sensitivity, specificity, PPV, NPV, PLR, and NLR of DMSA scan for predicting vesicourethral reflux was 0.75, 0.9, 0.33, 0.98, 7.5, and 0.27, respectively. Conclusions. Ultrasonography cannot predict the presence of VUR, but DMSA scan has a good sensitivity in this context. Therefore, by observation of DMSA scan results, it can be decided whether to perform VCUG or not.